LEMBAGA KEARSIPAN PERGURUAN TINGGI DI INDONESIA: BENTUK, TUGAS DAN KELENGKAPANNYA: Array - Zaenudin Zaenudin (Arsip Nasional Republik Indonesia, 2013)
In Indonesia, a university/college archives institution (UAI) is a new concept officially recognized by the law in conjunction with the Law Number 43 of 2009. However, the UAI has been established since 2004 in Indonesia, along with the launching of university archives of Gadjah Mada University. The Law legalizes the UAI as a University/College archives authorizing in managing records and archives for the institution and a new actor in that area. As a new actor, the UAI needs to be givenbetter attention both physics and non physics than the previous one especially related to assessment, mentoring and tutoring. The form of organization are still varies, though, there are still not enough organization tools such as records management file has not been established fully. As a records and archives manager, UAI shall have tasks to implement all records and management functions, for example, acquisition, arrangement and description, preservation and publicservice. On the other hands, the UAI shall have a responsibility for tutoring UAI archives at universities/colleges. To reach the outcomes, UAI should be given high quality and profesional human resources, adequate infrastructures, as well as sufficient budgets.